2016
DOI: 10.5606/tftrd.2016.54189
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to home-based exercise therapy in elderly patients with knee osteoarthritis

Abstract: Osteoarthritis (OA) is the most common chronic joint disorder causing pain and deformities and is an important cause of morbidity in elderly people. The knee is one of the most commonly involved joints and causes significant functional limitations. [1] The therapeutic management for OA patients is often divided into three main categories: nonpharmacological, pharmacological and surgical methods. Non-pharmacological treatment modalities recommended by European League Against Diz osteoartriti olan yaşlı hastalar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…A visual demonstration of the exercises, along with follow ups with a therapist for a maximum of two sessions, may have contributed to significant improvements in exercise technique, treatment adherence and, subsequently, BMs. Other studies reported that the demonstration of exercises is a more efficient way of prescribing home-based exercises [42][43][44]. Benefits of education for knee OA patients are well documented and results of the present study reinforce that supervised education should be part of any conservative treatment plan [1,2].…”
Section: Significance Of the Resultssupporting
confidence: 68%
“…A visual demonstration of the exercises, along with follow ups with a therapist for a maximum of two sessions, may have contributed to significant improvements in exercise technique, treatment adherence and, subsequently, BMs. Other studies reported that the demonstration of exercises is a more efficient way of prescribing home-based exercises [42][43][44]. Benefits of education for knee OA patients are well documented and results of the present study reinforce that supervised education should be part of any conservative treatment plan [1,2].…”
Section: Significance Of the Resultssupporting
confidence: 68%
“…The most-investigated strategy was the individual or group self-management course/program, investigated in 52% of the studies [ 19 , 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], which encompassed a mix of the remaining strategies. Following, the order of the most-investigated strategies was physical exercise (in 34% of the studies), that could be specific [ 32 , 52 , 53 , 54 , 55 ] or general exercises [ 20 , 21 , 25 , 35 , 48 , 49 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], individually or in groups, followed by education (in 21% of the studies) [ 21 , 32 , 36 , 52 , 53 , 54 , 56 ...…”
Section: Resultsmentioning
confidence: 99%
“…Most studies investigated more than one dependent variable, and most of them presented positive outcomes, yielding improvement of many symptoms after the practice of the chosen pain self-management strategy ( Table 2 ). The most evidenced positive outcome was related to pain itself (51.72%) [ 20 , 25 , 28 , 29 , 30 , 32 , 33 , 35 , 36 , 38 , 40 , 43 , 44 , 45 , 47 , 48 , 49 , 53 , 54 , 55 , 58 , 59 , 61 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 74 , 75 , 78 , 79 ]. Self-strategies investigated resulted in the reduction of pain intensity and/or the number of spots presenting pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the outbreak of the epidemic, home-based exercise was mainly used as aids for patient treatment or as means to restore physical function after surgery. Existing researches show that home-based exercise has good auxiliary effects on the treatment of fractures, osteoarthritis, and other musculoskeletal system diseases [5][6][7][8][9][10], cardio-cerebral vascular system diseases [11][12][13][14][15][16], respiratory system diseases [17][18][19], and even cancers [20][21][22][23]. Home-based exercise also has effects on supporting the treatment of nervous system diseases such as depression and Parkinson's disease [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%